2022
DOI: 10.1101/2022.02.13.480272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-modal single-cell and whole-genome sequencing of minute, frozen specimens to propel clinical applications

Abstract: Single-cell genomics are enabling technologies, but their broad clinical application remains challenging. We report an easily adaptable approach for single-cell transcriptome and T cell receptor (TCR)-sequencing, and matched whole-genome sequencing from tiny, frozen clinical specimens. We achieve similar quality and biological outputs while reducing artifactual signals compared to data from matched fresh tissue samples. Profiling sequentially collected melanoma samples from the KEYNOTE-001 trial, we resolve ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…These features enabled the extraction of new biological insights from a limited cohort of breast cancer patients. In a recent study, we applied Starfysh to disentangle the spatial dynamics of activated and exhausted T cell subsets in Slide-Seq V2 77 data from anti-PD-1 treated melanoma tumors 78 , showing its applicability to other ST technologies and cancer systems. In future work, the incorporation of archetypal analysis in the probabilistic framework and extensions to multi-omics integration with proteomics or chromatin accessibility will improve our ability to achieve comprehensive characterization of spatial heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…These features enabled the extraction of new biological insights from a limited cohort of breast cancer patients. In a recent study, we applied Starfysh to disentangle the spatial dynamics of activated and exhausted T cell subsets in Slide-Seq V2 77 data from anti-PD-1 treated melanoma tumors 78 , showing its applicability to other ST technologies and cancer systems. In future work, the incorporation of archetypal analysis in the probabilistic framework and extensions to multi-omics integration with proteomics or chromatin accessibility will improve our ability to achieve comprehensive characterization of spatial heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that these mechanisms are orthogonal to clinically validated mechanisms of resistance to immunotherapies, such as impaired antigen presentation 4,5 or IFN-ɣ-JAK/STAT signaling 3,33 . In addition to melanoma 7 , we also show that these mechanisms may play a role in kidney cancer patients treated with immune checkpoint blockade 21 . Furthermore, CD58 loss has previously been implicated in immune escape by hematological cancers 34-37 and has recently been identified as a mechanism of resistance to CD19-targeting CAR-T cells in patients with diffuse large B cell lymphoma (DLBCL) 20 .…”
Section: Discussionmentioning
confidence: 65%
“…Prior reports indicated that CD58 downregulation or loss is associated with cancer immune evasion and resistance to ICB in melanoma or CAR-T cell therapy in lymphoma [6][7][8]20 ; however, the underlying mechanisms are poorly understood. Analysis of The Cancer Genome Atlas (TCGA) indicates that baseline CD58 expression is variable in cutaneous melanoma and virtually absent in uveal melanoma, a rare subtype of melanoma that arises in the eye and has an extremely low response rate to immunotherapies (Fig.…”
Section: Intact Cancer Cell Cd58 Expression Is Necessary For Anti-tum...mentioning
confidence: 99%
See 1 more Smart Citation